Tootache and gum disease in Malay medical manuscript - Witjaksono, Widowati (2015)
Toothaches and gum diseases are commonly encountered and persistent problems in dentistry since Antiquity. In Malay medical manuscripts such as ar-Rahmah fi at-Tib and Tayyib al-Ihsan, some sections were devoted to the discussion on causes and treatments of these problems. The discussion may use some Arabic words which indicates influence from Arabic medicine or familiarity of the author with other medical texts. Many of the descriptions of the conditions stand in striking similarity to what is currently known in modern dentistry. As the manuscripts were written before the advent of disciplines such as microbiology and microscopy, for example, the idea behind the causes of these diseases, however, may need to be reassessed and put into context. Likewise, the prevailing ideas in the manuscript may be useful in modern context such as the type of treatments that were used may be reintroduced or tested in modern dentistry. The paper therefore will try to compare between what was written on dentistry in the manuscripts with what is currently known.